Clinicopathological characteristics and prognosis analysis of gastrinoma based on the SEER database - Chenjian Qiu; Chengru Hu; Chengjie Lu; Jingxian Shi; Zhenguo Qiao; Yaping Wang; Feidie Xu (PLoS ONE, 2025)
Gastrinoma, distinguished by Zollinger-Ellison Syndrome, is a highly unusual neoplasm. However, understanding of its clinicopathological characteristics and survival at the population level is inadequate. This study aimed to examine the clinicopathological features and survival of gastrinoma patients utilizing the Surveillance, Epidemiology, and End Results (SEER) database. Patients diagnosed with gastrinoma from 2000 to 2020 were included in the study. Multiple imputation was used to handle missing data. Chi-square test was employed to analyze the clinicopathological features. The Kaplan-Meier method and Cox proportional hazards models were utilized to evaluate overall survival (OS) and cancer-specific survival (CSS). A total of 160 patients participated in the study. The incidence rate rose with age, peaking at 60–69 years. Notably, the most common site was the pancreas (52.5%), followed by the duodenum (32.5%) and stomach (10.6%). Most gastrinomas were well-differentiated (77.5%). Liver was a frequent metastasis site, with age and tumor size identified as risk factors by multivariate analysis. The 1-, 3-, 5-, and 10-year OS rates were 92.4%, 84.3%, 77.6%, and 62.9%, respectively, with corresponding CSS rates of 94.8%, 89.2%, 86.0%, and 75.2%. Additionally, duodenal gastrinomas showed better differentiation, earlier staging, smaller size, and fewer metastases than pancreatic ones ( P < 0.05). Pancreatic gastrinomas had poorer OS (hazard ratio [HR] 2.38, 95% confidence interval [CI] 1.30–4.35, P = 0.005) and CSS (HR 10.70, 95% CI 2.55–44.90, P = 0.001) compared to duodenal ones. Multivariate Cox analysis highlighted N stage, surgery, chemotherapy, and tumor size as risk factors for both OS and CSS. Gastrinomas located in the duodenum and pancreas exhibit distinct clinicopathological characteristics. The prognosis for gastrinomas in the duodenum is better than that for gastrinomas in the pancreas.